Integrative Review: Teaching Strategies and Tools Used to Assess the Knowledge of Health Science Students Concerning Blood Pressure Measurement - Ferreira, Paulo Alexandre Carvalho (2014)
Abstract Introduction and objectives: Eventhough indirect blood pressure measurement is a non-invasive procedure, it poses theoretical and practical challenges. This study's aim was to investigate what has already been published concerning Health Science students' knowledge of blood pressure measurement, to identify the tools used to estimate this knowledge and the teaching strategies adopted. Methods: An integrative literature review was conducted. Research was carried out in four databases, using controlled and uncontrolled keywords. Results: With regard to the level of evidence, 75% of the eight studies selected were classified as level 6, 12.5% was classified as level 4, and 12.5% as level 3. Nursing students were assessed in 62.5% of the studies; pharmacology students in 12.5%; chiropractic students in 12.5%, and both nursing and medical students were assessed in 12.5% of the studies. In regard to teaching strategies, 50% of the studies assessed traditional teaching methods; 12.5% also used role-playing as a teaching strategy; 12.5% used an arm simulator for blood pressure measurement; 12.5% designed pedagogical games; and 12.5% adopted an extracurricular program with lectures, video tutorials, and developed skills in the laboratory. Conclusions: Most were observational studies assessing traditional teaching methods by means of nonvalidated questionnaires and checklists, following the recommendations of the American Heart Association. Pedagogical interventions were rare.